2013
DOI: 10.1261/rna.036319.112
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs are ligands of Toll-like receptors

Abstract: It has long been known that microRNAs (miRNAs) can regulate target gene expression at the post-transcriptional level. Recent studies, however, have revealed that miRNAs can also be transported from donor cells to recipient cells, in which these RNAs function in a novel manner as ligands of Toll-like receptors. Here, we review the latest findings on these unconventional miRNAs, with special emphasis on their biological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 10 publications
0
61
0
Order By: Relevance
“…miR-21 and miR-29a can bind to TLR 7 and TLR 8 as agonists, leading to NF-κB signaling activation and secretion of IL-6 and TNF-α, which locally promote cancer cell growth and metastasis when treating cancer, and may cause systemic immune toxicity [74]. miRNAs may bind to the TLR 7 and TLR 8 via the GU-rich motif (GUUG for miR-21 and GGUU for miR-29a), which is crucial for RNA–TLR recognition [75,76]. …”
Section: Current Challenges In Mirna Deliverymentioning
confidence: 99%
“…miR-21 and miR-29a can bind to TLR 7 and TLR 8 as agonists, leading to NF-κB signaling activation and secretion of IL-6 and TNF-α, which locally promote cancer cell growth and metastasis when treating cancer, and may cause systemic immune toxicity [74]. miRNAs may bind to the TLR 7 and TLR 8 via the GU-rich motif (GUUG for miR-21 and GGUU for miR-29a), which is crucial for RNA–TLR recognition [75,76]. …”
Section: Current Challenges In Mirna Deliverymentioning
confidence: 99%
“…Fragments of the viral genome, as well as virus-encoded small RNAs, such as those encoded by EBV, and certain host cell miRNAs, have been shown to trigger target cell PRRs. Although triggering of the PRR system results in complex responses, in some cases it may induce an increased activation status of these cells (37)(38)(39). Most of the described EV-mediated effects on the function of other cells are restricted to in vitro systems or occur within the same organism.…”
Section: "Mister Postman": What Do Evs and Viruses Delivermentioning
confidence: 99%
“…Exogenous factors may alter the function of this TLR leading to a defect of the innate immunity response. In this regard, it has been demonstrated that heat-shock proteins (49) and microRNAs (50) are ligands for TLR7 and that exogenous factors, in particular UV radiations, may deregulate their expression (51,52). As a consequence, under certain circumstances the TLR7 expression can be downregulated, diminishing its activity toward innate and acquired immunity, and consequently, also toward the control of UV-induced skin cancers.…”
Section: Discussionmentioning
confidence: 99%